The tree Acacia mangium (Fabaceae) facilitates the recovery of mining areas in the rain forest of Chocó, Colombia - Abella-Sanclemente, Carmen Sofia (2023)
Introduction: Mining-impacted areas in tropical forests require the application of ecological restoration strategies, but this process often involves use of exotic plant species ignoring the effects on the ecological regeneration of the sites where they are introduced. Objective: To evaluate the effect of Acacia mangium plantations (exotic plant) on early ecological rehabilitation (soil and vegetation) of areas impacted by open-pit gold mining in the tropical rain forest of Chocó, Colombia. Methods: 16 mining areas were selected as sampling units (eight reforested with A. mangium and eight in natural succession) in two locations. In each sampling unit, a 2 × 50 m plot was established (four plots per sampling scenario and locality), where soil fertility (physical and chemical parameters) was analyzed and the number of individuals of each vascular plant species was quantified. Results: 73 species (69 genera, 45 families) were recorded. The density of individuals was higher in areas of natural succession than in those reforested with A. mangium; conversely, species richness and diversity were higher under the A. mangium plantations. Floristic similarity was low between successional scenarios (shared species 35.6 %). The soil showed better conditions (especially N-NHO3) in mining areas with A. mangium than in those in natural regeneration. Conclusions: A. mangium plantations appears to facilitate the early rehabilitation of soil fertility and vegetation in abandoned mines; therefore, this species can play an important role in the implementation of ecological restoration strategies in areas impacted by open-pit gold mining in the Chocó and other tropical forest systems with similar environmental and disturbance conditions.